Issues of criminal-legal assessment of murder and scientific views of professor I. I. Gorelik - Gruntov, Igor O. (Journal of the Belarusian State University. Law, 2021)
Human life is an absolute blessing given to us by nature and is a fundamental value in our society and state. On this basis, murder is considered the most serious and most severely punishable crime. In this regard, the study of the objective and subjective signs and the qualifying circumstances of these crimes is associated with the correct criminal-legal assessment of the crime, the individualisation of punishment, the prevention and suppression of such acts committed. The theoretical study of the issues of understanding crimes against life, the study of their signs began in the second half of the 19th century, continued during the existence of the USSR and is being actively investigated at the present time. It should be noted importance of the theoretical views of professor I. I. Gorelik in this area. They acquire particular relevance on the eve of the centenary of the birth of the famous scientist.
Keywords: qualification of murder; object of criminal law protection; qualifying signs of murder; murder with special cruelty; murder based on hooligan motives